Under-5 mortality in Tanzania: a demographic scenario. - A Sathiya Susuman; Hamisi F Hamisi (Tehran University of Medical Sciences, 2012)
The government of the United Republic of Tanzania has initiated the Integrated Management of Childhood Illness program to improve the health and wellbeing of children.Tanzania's under-five mortality rate is still 1.7 times higher than the world average and, in order to achieve its Millennium Development Goal 4 target, its annual reduction rate is quite low at 2.2. The main aim of the study is to examine under-five mortality combined with the Data from the Tanzania Demographic and Health Survey 2008 data was used. Odds ratios for infant and under-five mortality were estimated using logistic regression; crude and adjusting models were adopted.Mortality cases (18.3%) have been reported to children born with an interval of